Dietary Protein Intake and Associated Risks for Atopic Dermatitis, Intrinsic Eczema, and Allergic Sensitization among Young Chinese Adults in Singapore/Malaysia: Key Findings from a Cross-sectional Study - Jun Jie Lim; Kavita Reginald; Yee-How Say; Mei Hui Liu; Fook Tim Chew (Elsevier, 2023)
Through an investigator-administered questionnaire that follows the standard protocol of the International Study of Allergy and Asthma in Childhood, data on symptomatic histories of eczema and dietary habits were collected from 11,494 young Chinese adults in Singapore/Malaysia. Allergic sensitization status was assessed through a skin prick test reactivity to common house dust mites. Using three dietary indices (dietary protein score, animal protein score, and plant protein score), the associations between atopic dermatitis, intrinsic eczema, allergic sensitization, and intake of various proteins were estimated. On average, most subjects frequently eat meat, vegetables, and rice in their diets. Through a multivariable logistic regression adjusted for age, sex, body mass index, and parental eczema, subjects with high dietary protein score (adjusted OR = 1.397; 95% confidence interval = 1.133-1.724; P < 0.003) and high animal protein score (adjusted OR = 1.353; 95% confidence interval = 1.106-1.682; P < 0.003) were associated with increased risk of atopic dermatitis. Interestingly, synergy factor analysis revealed that a higher intake of plant proteins than animal proteins in diets significantly reduced overall associated risks of atopic dermatitis and allergic sensitization but not those of intrinsic eczema. Most importantly, these associations are independent of dietary fat intake. Taken together, frequent adherence to diets rich in plant proteins reduced associated risks of atopic dermatitis in Singapore/Malaysia Chinese adults.